1995
DOI: 10.1046/j.1525-1438.1995.05010064.x
|View full text |Cite
|
Sign up to set email alerts
|

Previous hydatidiform mole identified as the causative pregnancy of choriocarcinoma following birth of normal twins

Abstract: For appropriate clinical management of patients with gestational trophoblastic tumors it is important to ascertain both the nature of the causative pregnancy and the time interval between that pregnancy and the diagnosis of the tumor. It has been shown that the immediately antecedent pregnancy may not be the causative pregnancy in some cases of choriocarcinoma, particularly where there is a history of molar pregnancy. We report further studies of a case where the causative pregnancy was shown to be a hydatidif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…Since the score assigned to abortion is one and that to mole is zero, correct identification of the index antecedent pregnancy affects the final score. To solve this, biomolecular method using the difference in marker chromosome or genetics between the father and mother can be used to identify molar pregnancy which is paternal in origin (13) .…”
Section: Practicality In Stagingmentioning
confidence: 99%
“…Since the score assigned to abortion is one and that to mole is zero, correct identification of the index antecedent pregnancy affects the final score. To solve this, biomolecular method using the difference in marker chromosome or genetics between the father and mother can be used to identify molar pregnancy which is paternal in origin (13) .…”
Section: Practicality In Stagingmentioning
confidence: 99%
“…35,36 It has been presumed that the androgenetic tumors are derived from a previous molar gestation, and this has indeed been proven to be so in several patients, by the showing of complete genetic identity between the mole and the choriocarcinoma, this despite the fact that in two such patients a full-term pregnancy with normal delivery had intervened between the molar pregnancy and the development of the choriocarcinoma. 33,34,37 In one of these patients, the time interval between the mole and the choriocarcinoma was 10 years, and it is difficult to understand how tissue from the mole remained in the uterus for that length of time, and throughout a later normal pregnancy, to then subsequently undergo a neoplastic resurgence, this typifying the questions posed by this enigmatic lesion.…”
Section: Originmentioning
confidence: 99%
“…Choriocarcinoma and PSTT are malignant tumors which arise from the trophoblasts of any kind of pregnancy, including hydatidiform mole. It has been shown that the causative pregnancy of GTNs is not necessarily the immediately antecedent pregnancy using DNA analysis (Fisher et al, 1995). …”
Section: Introductionmentioning
confidence: 99%